Network-risks: a matrix of interdependent urban networks' failures - Touili, Nabil (Belgeo, 2022)
International audience From a theoretical typology and empirical data derived from disaster events, this paper provides a matrix of cascading failures of interdependent infrastructures of energy, transport, telecommunications, water and sanitation, food systems and health services. High urbanisation has led to an expansion of networked infrastructure, whose failures are notably related to their numerous and complex interdependencies. A prior identification of these interdependencies is fundamental to prevent cascading failure risks. This paper identifies four types of interdependencies (functional, geo-spatial, procedural and societal) and examines their respective roles in the failures experienced during the 2017 hurricanes Irma and Maria, the 2001 World Trade Center attack, the 2011 Fukushima disaster, the 2011 eruption of the Icelandic volcano Eyjafjallajökull, the 2003 heat wave and the 2012 Indian blackout. A cross-network matrix is thus developed to address the following question: through which type(s) of interdependencies does the initial failure of a given infrastructure network trigger failures in interdependent networks? Our deductive approach reveals network-risks and identifies the types of interdependencies by which infrastructure networks represent a hazard sources and/or a vulnerable stake to one another. Unidirectional, reciprocal and mutual dependencies are then underlined. Accordingly, the continuous supply of urban services is thus explored within the perspective of increasing interdependencies. À partir d’une typologie théorique et de données empiriques tirées d’évènements catastrophiques, cet article fournit une matrice des défaillances des réseaux interdépendants d’énergie, de transport, de télécommunications, d’eau et d’assainissement, d’alimentation et de santé. La forte urbanisation a entraîné une expansion des réseaux d’infrastructures critiques, dont les défaillances sont notamment dues à leurs interdépendances multiples et de plus en plus complexes. L’identification préalable des ...